2000
DOI: 10.1128/mcb.20.23.8676-8683.2000
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of the Tissue-Specific Transcription Factor HNF4, a Potential Regulator in Early Xenopus Development

Abstract: Hepatocyte nuclear factor 4␣ (HNF4␣) is an orphan receptor of the nuclear receptor superfamily and expressed in vertebrates as a tissue-specific transcription factor in liver, kidney, intestine, stomach, and pancreas. It also plays a crucial role in early embryonic development and has been identified as a maternal component in the Xenopus egg. We now report on an activity present in Xenopus embryos that inhibits the DNA binding of HNF4. This HNF4 inhibitor copurifies with a 25-kDa protein under nondenaturing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…A series of coactivators have been identified that interact with defined regions of the HNF4 protein (listed in Sladek & Seidel 2001). No definitive ligand for HNF4 has been identified as the recent claim that fatty acylcoenzyme A thioesters might be ligands (Hertz et al 1998) has been challenged by the finding that these compounds exert only a minor effect and have a limited specificity (Peiler et al 2000, Sladek & Seidel 2001. Thus HNF4 remains an orphan receptor, but the identification of potential ligands is still an important issue as such compounds might be important in influencing HNF4 activity in the organism.…”
Section: The Tissue-specific Transcription Factor Hnf4mentioning
confidence: 99%
See 3 more Smart Citations
“…A series of coactivators have been identified that interact with defined regions of the HNF4 protein (listed in Sladek & Seidel 2001). No definitive ligand for HNF4 has been identified as the recent claim that fatty acylcoenzyme A thioesters might be ligands (Hertz et al 1998) has been challenged by the finding that these compounds exert only a minor effect and have a limited specificity (Peiler et al 2000, Sladek & Seidel 2001. Thus HNF4 remains an orphan receptor, but the identification of potential ligands is still an important issue as such compounds might be important in influencing HNF4 activity in the organism.…”
Section: The Tissue-specific Transcription Factor Hnf4mentioning
confidence: 99%
“…Thus HNF4 remains an orphan receptor, but the identification of potential ligands is still an important issue as such compounds might be important in influencing HNF4 activity in the organism. Recently, a low molecular compound has been identified in embryonic extracts of Xenopus that inhibits quite specifically the DNA binding properties of HNF4 (Peiler et al 2000). However, this inhibitor is distinct from the usual ligands of the nuclear hormone receptor superfamily, as it does not require the ligand binding domain of HNF4 to exert its inhibitory function.…”
Section: The Tissue-specific Transcription Factor Hnf4mentioning
confidence: 99%
See 2 more Smart Citations
“…an HNF-4α inhibitor is abundantly present in Xenopus embryos, in which the HNF-1 gene is only marginally expressed, 42) we propose that similar kinds of inhibitors might be present in RLE cells to restrict the activity of the HNF-4α.…”
Section: Discussionmentioning
confidence: 99%